Design of an exoskeleton for lifting - Lim, Ernest Zhen Xuan (Nanyang Technological University, 2024)
Lower back injuries, caused by muscle strain around the lumber spine, are common in work involving manual labour. Through this study, a lightweight and comfortable exoskeleton is designed to alleviate the issue. The design of the exoskeleton utilizes spring tension to achieve an assisting moment arm which provide support in lifting tasks. The final prototype was assembled from stainless steel rods, aluminium plates, and 3D printed components. The rods and plates were cut to the required dimensions through the milling and lathe machines. 3D printed components were modelled with SolidWorks, a computer-aided design (CAD) software. Calculations and experiments were performed to verify the exoskeleton’s significance and effectiveness in assisting users. Muscle force was calculated to determine the effectiveness of the prototype. Comparison was made to determine validity of theoretical calculations after the conducted experiments. The exoskeleton was deemed to be capable of providing significant assistance to the body in lifting heavy loads. Improvements could be made selecting the materials used to manufacture the actual product. A height adjusting mechanism could be added in future works.